Aqueous coating composition and use thereof
Patent Information
- Application Number
- JP2023141954
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-09-02
- Filing Date
- 2023-09-01
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-09-01
AI Technical Summary
Existing coatings for fasteners like bolts and screws rely on fluorinated polymers like PTFE to set the coefficient of friction, which are environmentally harmful and costly, and lack effective solutions for heat dissipation and stick-slip effects, especially in aqueous systems.
An aqueous coating composition using a copolymer of unsaturated hydrocarbons and unsaturated carboxylic acids, combined with lubricants and optional additives, to achieve a tunable coefficient of friction without fluorinated polymers, addressing heat dissipation and stick-slip issues.
The composition provides a reproducible and stable coefficient of friction within the desired range, reducing environmental impact and operational uncertainties, suitable for industrial applications including robotic screw tightening.
Smart Images

Figure 2024035828000001
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of coatings, in particular coatings for bulk materials. In particular, the present invention relates to an aqueous coating composition for producing a coating having a tunable coefficient of friction. Furthermore, the present invention relates to a method for producing a coating having a tunable coefficient of friction and to the use of the aqueous coating composition for producing a coating having a tunable coefficient of friction. Finally, the present invention relates to a coated substrate. [Background technology]
[0002] Fastening parts, especially small parts such as bolts, nuts and screws, used to mechanically fasten parts, especially metal parts, need to have a specific and reproducible coefficient of friction so that they can be processed industrially. The coefficient of friction μ indicates the ratio of normal force to frictional force, the higher the coefficient of friction, the higher the frictional force. The higher the frictional force, the less energy is transferred to the elastic or plastic elongation of the thread during the tightening process, resulting in a reduction in the so-called preload force. The preload force is usually specified to ensure reliable performance of bolted joints, which is why the coefficient of friction must work within a specified window. This is especially important for fastening materials, such as bolts, screws, nuts or even rivets, since they are used to completely mechanically fasten parts. On the one hand, the friction must be high enough to prevent unintentional loosening of the compound, but at the same time low enough to allow a perfect material-material bond.
[0003] Furthermore, the coefficient of friction must be set as constant as possible, in order to allow industrial processing, especially with robots, for example for screws with a defined torque or bolt rivets with always the same force. For this reason, small fastening parts are often coated in practice with a specific coating composition in the form of a topcoat intended to set and influence the sliding and frictional properties of the part in a desired manner. The desired sliding and frictional properties of a screw or bolt are usually determined in accordance with DIN EN ISO 16047:2013-01, in which the German Association of the Automotive Industry (VDA) specifically specifies a window of friction coefficient μ between 0.09 and 0.16 for screws.
[0004] To set a desired coefficient of friction, certain topcoat compositions usually contain fluorinated plastic particles, especially based on polyfluorotetraethylene (PTFE) or polyvinylidene fluoride (PVDF). However, the use of fully or partially fluorinated compounds has some serious drawbacks: on the one hand, fluorinated polymers are relatively expensive, and on the other hand, they should be avoided from the viewpoint of environmental protection. During the production of fluorinated compounds, especially PTFE, not insignificant amounts of perfluorooctanoic acid (PFOA) are usually produced or used for the production of these compounds. Perfluorooctanoic acid is practically non-degradable in nature, accumulates in the body, and is particularly liver-damaging, reproductively toxic, and carcinogenic. The production of perfluorooctanoic acid and its precursor compounds has therefore been banned in the European Union since July 4, 2020, with few exceptions. PTFE can be purified with respect to PFOA, so that PFOA-free PTFE can be used, but this is energy intensive and makes the extraction of the raw materials more expensive. PTFE itself is difficult to disperse in aqueous media and is not degradable in nature, it is a so-called non-degradable material, and therefore should be replaced by more environmentally compatible raw materials. Furthermore, the production or use of PTFE also produces polyfluorinated by-products and decomposition products, which should not be released into the environment if possible.
[0005] For this reason, efforts are being made to replace polyfluorinated plastics with other materials as far as possible, but this is often not easy, since polyfluorinated or perfluorinated plastics have special and sometimes outstanding properties, especially with regard to their hydrophobic wetting or non-wetting properties, their resistance to chemical and physical properties, and their excellent sliding properties. One problem that arises especially in screwed joints is the heat dissipation behavior, since the sliding properties of many plastics change with increasing temperature. In particular, the sliding properties of many plastics improve when heated. However, this is not desirable for screwed joints, since there is otherwise a risk of unintentional loosening of the joint. Perfluorinated plastics, in particular PTFE and PVDE, do not exhibit this problematic behavior or only to a limited extent, so that they are still the materials of choice today to set the sliding or frictional properties of fasteners in a targeted manner. PTFE is particularly characterized by its high melting point, which allows the frictional behavior to be optimized in a higher temperature range.
[0006] Another problem that occurs especially when the screw is tightened at high speed is the so-called stick-slip effect, also known as jerk slip. In this case, the screw does not move smoothly during tightening, but instead starts to stick and slip. This can result in torque uncertainties on the one hand and preload uncertainties on the other hand, which in turn can lead to hidden risks of failure during operation. The stick-slip effect should therefore be avoided as far as possible, which is why the sliding and adhesive properties of the bolt need to be set particularly precisely and uniformly. Up to now, the stick-slip effect can only be largely prevented by using topcoats that contain fluorinated polymers. However, one drawback of fluorinated polymers is that, due to their hydrophobicity, they should be used preferentially in solvent-based systems, although for reasons of environmental protection and occupational safety, water-based systems are increasingly preferred. To date, the state of the art is lacking a water-based coating system that allows targeted targeting of the coefficient of friction, especially for small fasteners, and manages to achieve while meeting the requirements for a narrowly defined coefficient of friction window, heat dissipation and stick-slip behavior without the use of PTFE, and preferably without the use of any fluorinated polymers. Summary of the Invention
[0007] It is therefore an object of the present invention to provide a coating composition which allows for the precise setting of the coefficient of friction of parts, in particular fastening parts, such as in particular screws, nuts, bolts or rivets, and which furthermore does not require the use of PTFE, and preferably does not require any fluorinated polymers at all. It is a further object of the present invention to provide a coating system that is at least substantially free of organic solvents, and preferably free of organic solvents. It is a further object of the present invention to provide a coating system which largely prevents the stick-slip effect. The subject matter of the invention according to a first aspect is therefore an aqueous coating composition as defined in claim 1, further advantageous embodiments of this aspect of the invention being the subject matter of the associated dependent claims. Furthermore, another subject of the present invention according to a second aspect is the use of a coating composition according to claim 15. Further subject matter of the invention according to a third aspect thereof is a method for producing a coating according to claim 16, further advantageous embodiments of this aspect of the invention being the subject matter of the associated dependent claims. Finally, a further subject matter of the invention according to a fourth aspect is a metal substrate as claimed in claim 18, further advantageous embodiments of this aspect of the invention being the subject matter of the associated dependent claims.
[0008] It will be appreciated that certain characteristics, features, embodiments, advantages, etc., are described below with respect to only one aspect of the invention in order to avoid unnecessary repetition, and naturally apply, as appropriate, to other aspects of the invention without the need for explicit mention. Furthermore, it applies that all values or parameter data etc. stated below can in principle be measured or can be measured by standardized or clearly stated measuring methods or measuring methods which are well known to the person skilled in the art. Additionally, it will be appreciated that all mass or amount related percentages will be selected by one of ordinary skill in the art to add up to 100%. With these conditions stated, the invention will now be explained in more detail. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Therefore, the present invention 1. The subject matter of the present invention according to an embodiment is an aqueous coating composition for producing a coating, in particular a topcoat, with a tunable coefficient of friction, comprising: (a) an organic binder comprising a copolymer of at least one unsaturated hydrocarbon and at least one unsaturated carboxylic acid; and (b) a coating composition comprising a lubricant. The applicant has surprisingly found that when a coating composition is used that contains an organic binder that contains at least one unsaturated hydrocarbon, in particular a copolymer of an olefin and at least one unsaturated carboxylic acid, and a lubricant, a topcoat with excellent sliding and friction properties can be obtained. Such coating compositions can be easily prepared in an aqueous medium, and furthermore, may be free of PTFE. Preferably, they even do not contain any fluorinated polymer. Thus, the present invention provides a system free of both solvents and fluoropolymers, particularly PTFE, that allows the ready availability of a topcoat that allows the coefficient of friction to be set to the value required for industrial production.The coating composition of the present invention is therefore superior from both an environmental and occupational safety standpoint to the conventional fluoropolymer-containing solvent-based systems known up to now.
[0010] Preferably, the organic binder already has certain slip properties. These slip properties of the binder are achieved in particular by the segments built up from polymerized unsaturated hydrocarbons of the copolymer, in particular polymerized olefins. The polar groups of the carboxylic acids make the polymer remain water-soluble or at least water-dispersible despite the presence of hydrophobic regions. It has been shown that when a lubricant is added to the organic binder, the sliding properties are further improved and the coefficient of friction can be stably set, especially at elevated temperatures. In the context of the present invention, a lubricant is understood to be a chemical substance or mixture of substances that changes the tribological properties of the coating, in particular reducing friction. In the context of the present invention, the lubricant can be in liquid or solid form, with the use of solid lubricants being preferred.
[0011] As already mentioned, in the context of industrial production, in particular robotic screw tightening, it is essential that the sliding properties or friction coefficients of coated fasteners, in particular screws, always assume comparable values in a reproducible manner. For this reason, VDA Guideline 235-101 specifies so-called friction coefficient windows in which the friction coefficients μ of fastening means, in particular bolts, nuts and screws, can be located. This friction coefficient window spans the interval of friction coefficients μ between 0.09 and 0.16. The friction coefficients are measured in accordance with DIN EN ISO 16047:2013-01. If other friction coefficient windows are specified and desired, these can also be met by the described inventive approach.
[0012] In the context of the present invention, it is preferred that the surfaces or coated substrates coated with the coating compositions of the present invention have a coefficient of friction μ, measured according to DIN EN ISO 16047:2013-01, in the range of 0.09 to 0.16. In the case of a screw, the coefficient of friction can be measured both on the thread and on flat surfaces, especially on the head of the screw. This double measurement is necessary because workpieces, especially threaded components, have different coefficients of friction on the thread and on flat coated surfaces, such as the head of the screw. For example, a screw designed as an internal support has a higher coefficient of friction and therefore poorer sliding properties on the thread than the head of a screw that is on a nut or screw washer. If the screw is an external support, the coefficient of friction will be higher on the head than on the thread. Because measuring the coefficient of friction of the entire workpiece includes measuring the coefficient of friction of both areas (threads and flat surfaces), workpieces coated with coatings that do not contain lubricants often have undesirably high coefficients of friction. However, in accordance with the present invention, the use of lubricants can be omitted. Within the scope of the present invention, it is preferably provided that for threaded parts, e.g. screws, the coefficients of friction of both the thread and the flat surface, respectively, lie within the above-mentioned coefficient of friction window of a coefficient of friction μ between 0.09 and 0.16.
[0013] Since the test rules described in DIN EN ISO 16047:2013-01 apply to single fastenings, the test arrangements for multiple fastenings are further specified in the test sheets according to VDA 235-203. Within the scope of the present invention, it is preferably further provided that the above-mentioned friction coefficient window for a friction coefficient μ of 0.09 to 0.16 is also met in the case of multiple tightening of both threads and flat surfaces. Furthermore, the thermal loosening behavior of workpieces, especially fasteners such as screws or bolts, is also important, especially if they are installed in assemblies, for example close to the engine. For this reason, VDA test sheet 235-203 specifies the preparation of tests at a temperature load of 150° C., where the friction coefficient window μ of 0.06 must not be undershoot. Within the scope of the present invention, it is therefore preferred that the workpiece coated with the coating composition of the present invention has a coefficient of friction μ in the range of 0.09 to 0.16 according to VDA test sheet 235-203 at 150° C. This coefficient of friction window is preferably filled for both the total coefficient of friction and, in the case of a threaded workpiece, both the thread and the flat surface.
[0014] In the context of the present invention, unsaturated hydrocarbons are understood as organic compounds, preferably non-polar, having at least one unsaturated bond, in particular at least one carbon-carbon double bond or carbon-carbon triple bond.Unsaturated hydrocarbons are primarily alkenes and alkynes, in particular compounds having vinyl and / or alkenyl groups, although aromatics and heteroaromatics having alkene or alkyne side chains, in particular vinyl and / or alkenyl groups, are also included.Furthermore, the hydrocarbons may also be substituted, for example by halide, and alcohol, amine or thiol functional groups.However, preferentially, the hydrocarbons are unsubstituted hydrocarbons, i.e. alkenes and alkynes or mixtures thereof. In the context of the present invention, unsaturated carboxylic acids refer to carboxylic acids with a carbon-carbon double bond or a carbon-carbon triple bond. In addition to the acidic group, the carboxylic acid may also be provided with further functional groups, in particular alcohol, thiol, amine and ether functional groups. Carboxylic acids also include in particular derivatives of carboxylic acids, in particular their esters and amides. In the light of the present invention, it is more preferred that the copolymer of at least one unsaturated hydrocarbon and at least one unsaturated carboxylic acid is a block copolymer.In this light, it is more preferred that the block copolymer has a block of segments of unsaturated hydrocarbon.Unsaturated hydrocarbons especially contribute to the fact that the binder of coating composition, especially topcoat composition, already has excellent slip properties and allows the setting of friction coefficient in a targeted manner.
[0015] Typically, in accordance with the present invention, it is provided that the unsaturated hydrocarbon is selected from the group of aliphatic hydrocarbons with vinyl groups, aromatic hydrocarbons with vinyl groups, aliphatic hydrocarbons with alkynyl groups, aromatic hydrocarbons with alkynyl groups and mixtures thereof.The results obtained are particularly obtained when the unsaturated hydrocarbon is selected from the group of aliphatic hydrocarbons with vinyl groups, aromatic hydrocarbons with vinyl groups and mixtures thereof.It is more preferred when the unsaturated hydrocarbon is an aliphatic hydrocarbon with vinyl groups.The unsaturated hydrocarbon is preferably an alkene and / or an alkyne, as mentioned above, and is preferably an alkene. The use of hydrocarbons with vinyl groups or alkenes makes it possible, in particular, to produce non-polar segments in the copolymer that can impart slip properties to the binder or coating, thereby facilitating the adjustment of the specific coefficient of friction.
[0016] Within the scope of the present invention, the unsaturated hydrocarbon is an aliphatic and / or aromatic C2-C 20 Compounds, aliphatic and / or aromatic C2-C with vinyl groups 20 Compounds and mixtures thereof, in particular aliphatic and / or aromatic C2-C 12 Compounds, aliphatic and / or aromatic C2-C with vinyl groups 12 Compounds and mixtures thereof, preferably aliphatic and / or aromatic C2-C 10 Compounds, aliphatic and / or aromatic C2-C with vinyl groups 10Particularly good results are obtained when the unsaturated hydrocarbon is selected from the group of aliphatic C2-C4 alkenes with vinyl groups, preferably aliphatic and / or aromatic C2-C8 compounds with alkynyl groups, aliphatic and / or aromatic C2-C8 compounds with vinyl groups and mixtures thereof, in particular aliphatic C2-C6 compounds with vinyl groups, more preferably aliphatic C2-C4 alkenes with vinyl groups, particularly preferably C2 and C3 alkenes. It is often indicated when the unsaturated hydrocarbon is selected from the group of aliphatic C2-C4 alkenes with vinyl groups. In light of this, it is even more preferred when the unsaturated hydrocarbon is selected from C2 and C3 alkenes and mixtures thereof. In light of the present invention, it is even more preferred when a C2 alkene, i.e. ethene, is used.
[0017] In the context of the present invention, it is also preferred that the unsaturated hydrocarbon is selected from the group of styrene, 1-hexene, 1-pentene, 1-butene, 2-butene, propyne, ethyne, 1-hexene, 1-pentene, 1-butene, 2-butene, propene, ethene and mixtures thereof.Preferentially, the unsaturated hydrocarbon is selected from the group of 1-hexene, 1-pentene, 1-butene, 2-butene, propene, ethene and mixtures thereof.Particularly good results are obtained when the unsaturated hydrocarbon is selected from styrene, 1-butene, 1-propene, ethene and mixtures thereof, in particular 1-butene, 1-propene, ethene and mixtures thereof, preferably propene, ethene and mixtures thereof.In the context of the present invention, it is even more preferred when the unsaturated hydrocarbon is ethene.
[0018] As far as the unsaturated carboxylic acid is concerned, it can be chosen from a wide range of compounds. However, it has been shown to be advantageous when the unsaturated carboxylic acid is chosen from alkenoic acids. 20 Alkenic acids, especially C2-C 12 Alkenic acids, preferably C2-C 10Particularly good results are obtained in this case with alkenoic acids, preferentially C2-C4 alkenoic acids and particularly preferentially C2-C3 alkenoic acids, and their esters and amides. Preferably, however, it is intended that the unsaturated carboxylic acids be used as the free acid. In the context of the present invention, the unsaturated carboxylic acid is acrylic acid, acrylic acid and C1-C 10 Esters with alcohol, methacrylic acid, methacrylic acid and C1-C 10 It is often indicated that the unsaturated carboxylic acid is selected from the group consisting of acrylic acid, acrylic acid and C1-C esters with alcohols, fumaric acid, maleic acid, and mixtures thereof. 10 Ethers with alcohols, methacrylic acid and methacrylic acid with C1-C 10 Particularly good results are obtained when the ester is selected from the group consisting of esters with alcohols and mixtures thereof.
[0019] In the context of the present invention, it is even more preferred that the unsaturated carboxylic acid is selected from the group consisting of acrylic acid, methyl acrylate, ethyl acrylate, butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate and hexyl methacrylate. In this context, it is particularly indicated that the unsaturated carboxylic acid is selected from the group consisting of acrylic acid, methyl acrylate, ethyl acrylate, methacrylic acid, methyl methacrylate and ethyl methacrylate, preferably acrylic acid and methacrylic acid.
[0020] As far as the molecular weight of the copolymer is concerned, this can of course vary over a wide range, but it is often indicated that the copolymer has a weight-average molecular weight Mw in the range from 2,000 to 250,000 g / mol, in particular from 5,000 to 200,000 g / mol, preferably from 10,000 to 150,000 g / mol and preferentially from 15,000 to 100,000 g / mol. The molecular weight of the polymeric compounds indicated in the context of the present invention refers to the weight-average molecular weight Mw, which is the weight of the individual polymeric compounds weighted by their mass fraction. The molecular weight or molecular weight distribution can be measured by various standardized procedures and methods, such as light scattering, rheology, mass spectrometry, permeation chromatography, etc. However, the methods used to measure the molecular weight distribution are well known to those skilled in the art and do not require further explanation. For example, the molecular weight of the polymers used can be measured, in particular, by the GPC method, in particular based on DIN 55672, with polymethyl methacrylate or polystyrene as standards.
[0021] The coating composition can contain the organic binder in almost any amount, however it is often indicated that the coating composition contains the organic binder in an amount of 2 to 70% by weight, in particular 5 to 60% by weight, preferably 10 to 50% by weight, preferentially 10 to 40% by weight, based on the coating composition. As already mentioned, the coating composition comprises a lubricant. Preferentially, the lubricant is selected from the group consisting of organic lubricants, inorganic lubricants and mixtures thereof. However, in the context of the present invention, particularly good results are obtained when the lubricant is an organic lubricant.
[0022] The lubricants used in the context of the present invention are usually in particulate form, in which respect they typically have an absolute particle size in the micrometer range. Particularly good results are obtained in accordance with the present invention when the lubricant is selected from the group consisting of wax, graphene, graphite, boron nitride, molybdenum disulfide, plastic particles, in particular polyetherketone (PEK), polyetheretherketone (PEEK), polyphenylene sulfide (PPS), polyethersulfone (PES), polyetherimide (PEI), polyamideimide (PAI) and mixtures thereof, finely divided sulfur and mixtures thereof.Preferentially, the lubricant is selected from the group consisting of wax, graphene, graphite, boron nitride, molybdenum disulfide and mixtures thereof.Particularly good results are obtained in accordance with the present invention when the lubricant is wax. In the context of the present invention, waxes are understood as substances, in particular natural or artificially obtained, that are usually kneadable at 20° C., solid to brittle and hard, coarse to finely crystalline, translucent to opaque but not glassy, and melt above 40° C. without decomposition. Above their melting point, even slightly, waxes usually have a relatively low viscosity and are not stringy. Waxes differ from similar synthetic or natural products mainly in that they usually change into a molten, low-viscosity state between about 50 and 90° C., exceptionally up to about 200° C., and are practically free of ash-forming components. Waxes form pastes or gels and usually burn with a sooting flame. Depending on their origin, waxes are divided into three groups: natural waxes, semi-synthetic waxes and synthetic waxes. Natural waxes are in particular vegetable waxes, such as candelilla wax, carnauba wax or montan wax, animal waxes, such as beeswax, lanolin and brushing lipids, mineral waxes, such as ceresin and ozokerite, and petrochemical waxes, in particular vaseline, kerosene wax and microwax.Semi-synthetic waxes are in particular hard waxes, such as montan ester wax and hydrogenated jojoba wax.Synthetic waxes are, for example, polyalkylene waxes or polyethylene glycol waxes.
[0023] When the lubricant is a wax, it is often indicated that the wax is selected from the group consisting of natural waxes, semi-synthetic waxes, synthetic waxes and mixtures thereof. Preferentially, the wax is a synthetic wax. Likewise, it is preferred in the context of the present invention that the wax is selected from the group of beeswax, carnauba wax, montan wax, modified montan wax, amide wax, polypropylene wax, polyethylene wax, HDPE wax (high density polyethylene wax), oxidized HDPE wax, ethylene vinyl acetate wax, polyethylene glycol wax, polyester wax, Fischer-Tropsch wax and mixtures thereof, preferentially polypropylene wax, polyethylene wax, HDPE wax, oxidized HDPE wax, ethylene vinyl acetate wax, polyethylene glycol wax, polyester wax, Fischer-Tropsch wax and mixtures thereof.
[0024] In this regard, particularly good results are obtained when the wax is selected from the group consisting of polypropylene waxes, polyethylene waxes, HDPE waxes, oxidized HDPE waxes, Fischer-Tropsch waxes and mixtures thereof. Even more preferably, in the context of the present invention, the wax is a polyethylene wax (PE wax). Waxes, especially synthetic waxes, preferably polyethylene waxes, can be used as lubricants to set the sliding and frictional properties of the coating composition. In particular, the combination of organic binders and wax-based lubricants shows excellent and consistent coefficients of friction, especially under multiple clamping and thermal stress.
[0025] Here, as far as the amount in which the coating composition contains the lubricant is concerned, this can vary within wide limits, but it has been found to be preferable if the coating composition contains the lubricant in an amount of 0.1 to 10% by weight, in particular 0.3 to 8% by weight, preferably 0.5 to 5% by weight, preferably 0.8 to 4% by weight, based on the coating composition. In accordance with the present invention, it is advantageously provided that the coating composition is free of fluorine-containing compounds, in particular free of organic fluorine-containing compounds.In accordance with the present invention, it is even more preferably provided that the coating composition is free of fluorinated polymer particles, in particular free of PTFE and PVDF. It is a great advantage of the present invention to provide coating compositions with selectively adjustable coefficients of friction that are free of the use of fluorinated polymer particles of concern. In particular, within the scope of the present invention, it is possible to provide coating compositions with excellent slip and friction properties that are completely free of the use of fluorinated organic compounds. Within the scope of the present invention it can furthermore be provided that the coating composition comprises at least one thickener and / or rheological additive.
[0026] The thickeners and / or rheological additives serve inter alia to set the viscosity and even the flow or layer thickness with which the compositions of the invention can be applied to a substrate. If the coating composition comprises a thickener and / or a rheological additive, the coating composition typically comprises the thickener and / or the rheological additive in an amount of 0.01 to 5% by weight, in particular 0.05 to 3% by weight, preferably 0.1 to 2% by weight, based on the coating composition. The thickening agent and / or rheological additive can be selected from a variety of suitable compounds and classes of compounds. However, it is often indicated that the thickening agent and / or rheological additive is selected from the group of ethyl cellulose, silicic acid and mixtures thereof. More preferably, the thickening agent and / or rheological additive is silicic acid, in particular fumed silica.
[0027] According to another preferred embodiment of the present invention, the coating composition comprises (a) an organic binder comprising a copolymer of at least one unsaturated hydrocarbon and at least one unsaturated carboxylic acid; (b) Lubricants, and (c) Contains thickeners and / or rheological additives. For this preferred embodiment of the invention, all advantages, properties and particular features mentioned above in the context of the further embodiments and properties of the coating composition of the invention apply as appropriate. Furthermore, in accordance with the present invention it can be provided that the coating composition comprises platelet-shaped particles.
[0028] In the context of the present invention, platelet-shaped particles, often also called flaky particles, are understood as particles whose thickness is significantly smaller than their length and width, i.e. whose extent in one spatial direction is significantly smaller than in the other two spatial directions. Usually, the aspect ratio, i.e. the ratio of the particle length or width to the particle thickness, is in the range of 2:1 to 100:1, in particular 4:1 to 50:1, preferably 5:1 to 20:1, preferentially 8:1 to 15:1. The platelet-shaped particles are preferably selected from the group consisting of metal flakes, glass flakes, layered silicates and mixtures thereof. The layered silicates are preferably selected from the group consisting of mica, talc, bentonite, kaolin and mixtures thereof. In this context, the metal flakes are preferably selected from the group consisting of aluminum flakes, zinc flakes, copper flakes and mixtures thereof. Preferably, the platelet-shaped particles are metal flakes, in particular selected from the group of aluminium flakes, zinc flakes, copper flakes and mixtures thereof. More preferably, the platelet-shaped particles are aluminium flakes. If the coating composition comprises platelet-shaped particles, the coating composition typically comprises the platelet-shaped particles in an amount of 0.3 to 8% by weight, preferably 0.5 to 5% by weight, preferentially 0.8 to 4% by weight, based on the coating composition. In light of this, particularly good results are obtained if the coating composition comprises a total amount of lubricant and platelet-shaped particles in the range of 0.5 to 20% by weight, in particular 1 to 18% by weight, preferably 1.5 to 15% by weight, preferably 2 to 12% by weight, based on the coating composition.
[0029] The further use of platelet-shaped particles in the coating composition allows the friction coefficient and sliding properties of the coated substrate to be precisely set, and in particular the stick-slip effect to be even better avoided. Furthermore, the use of platelet-shaped particles also allows the coating composition to be dried or cured at high temperatures without observing an increase in the friction coefficient. This is surprising, since the topcoat containing a lubricant, especially when it contains a wax, has a higher friction coefficient after exposure to temperature, especially after drying at high temperatures. This is due in particular to the fact that the lubricant, especially the wax, enters the gas phase or is pyrolyzed during the drying process. Surprisingly, the topcoat containing platelet-shaped particles in addition to the lubricant does not show this increase in the friction coefficient. Without being bound by theory, this is probably due to the fact that the platelet-shaped particles act as a diffusion barrier, on the one hand preventing the penetration of oxygen into the coating, thereby slowing down the decomposition of the lubricant, and on the other hand preventing the lubricant from entering the gas phase when a vaporizable or sublimable lubricant is used. Particularly good results are obtained when the mass ratio of the platelet-shaped particles to the lubricant is 1:0.8 to 1:1.8, in particular 1:1 to 1:1.6, preferably 1:1.1 to 1:1.4, based on the mass of the platelet-shaped particles and the mass of the lubricant in the coating composition.
[0030] According to a preferred embodiment of the present invention, the coating composition comprises (a) an organic binder comprising a copolymer of at least one unsaturated hydrocarbon and at least one unsaturated carboxylic acid; (b) a lubricant; (c) thickeners and / or rheological additives, and (d) Contains platelet-shaped particles. For this preferred embodiment of the invention, all advantages, properties and particular features mentioned above in the context of the further embodiments and properties of the coating composition of the invention apply as appropriate. Furthermore, it can be provided that the coating composition comprises at least one further additive.
[0031] If the coating composition comprises further additives, the coating composition comprises the further additives in an amount of 0.01 to 5% by weight, in particular 0.05 to 3% by weight, preferably 0.1 to 2% by weight, based on the coating composition. In view of this, particularly good results are obtained when the further additives are selected from the group of wetting agents, preservatives, stabilizers, acids and / or bases, defoaming components, film formers, levelling agents, UV absorbers, fillers, pH stabilizers and pH adjusters.
[0032] According to a preferred embodiment of the present invention, therefore, (a) an organic binder comprising a copolymer of at least one unsaturated hydrocarbon and at least one unsaturated carboxylic acid; (b) a lubricant; (c) thickeners and / or rheological additives, and (d) Platelet shaped particles; (e) A coating composition is provided that includes additional additives. For this particular embodiment of the invention, all advantages, properties and particular features mentioned above in the context of further embodiments and properties of the invention apply as appropriate.
[0033] According to a preferred embodiment of the present invention, the coating composition further comprises inorganic binder.The addition of inorganic binder improves the wear resistance and mechanical resistance of coating in particular.In addition, the use of inorganic binder is also commercially desirable, since they are often cheap to produce or obtain on a large industrial scale.When the coating composition comprises inorganic binder, inorganic binder is typically a silicon-containing binder. Preferably, the inorganic binder is selected from silanes, silane hydrolysates, silicates, polysiliconates and mixtures thereof. In view of this, particularly good results are obtained when the inorganic binder is selected from the group consisting of silanes, in particular trialkoxysilanes and tetraalkoxysilanes, preferably vinylsilanes, aminesilanes, phenoxysilanes and / or epoxysilanes, tetraethyl orthosilicate (TEOS), tetramethyl orthosilicate (TMOS), silane hydrolysates, colloidal silicic acid, water glass or silicates, in particular lithium water glass, sodium water glass, potassium water glass and mixtures thereof.In particular, the silanes that can be preferably used are those mentioned below for the preparation of silane-modified silicates.
[0034] According to a preferred embodiment of the present invention, the inorganic binder is especially free of lithium compounds. Within the scope of the present invention, particularly good coating and slip properties can also be obtained when the normally preferred lithium polysilicate (lithium water glass) is not used. This is a notable advantage of the present invention, since the demand for lithium and the subsequent price of lithium are expected to increase due to the increasing use of lithium-ion batteries and lithium-ion accumulators, especially in the automotive sector. Preferably, the inorganic binder is selected from the group of silanes, especially trialkoxysilanes and tetraalkoxysilanes, preferably vinylsilanes, aminesilanes, phenoxysilanes and / or epoxysilanes, tetraethyl orthosilicate (TEOS), tetramethyl orthosilicate (TMOS), silane hydrolysates, colloidal silicic acid (silica sol), sodium water glass, potassium water glass and mixtures thereof. More preferably, the inorganic binder is selected from the group of sodium water glass, potassium water glass and mixtures thereof.
[0035] According to a preferred embodiment of the invention, the inorganic binder comprises or consists of a mixture of water glass and / or colloidal silicic acid with a silane hydrolysate and / or a silane. Preferably, the inorganic binder comprises a mixture of water glass and / or colloidal silicic acid with a silane hydrolysate and / or a silane. These mixtures also do not show carbonation at alkaline pH values. According to this embodiment, it is preferred that the organic binder comprises waterglass and / or colloidal silicic acid in a weight ratio with the silane hydrolysate and / or silane in the range of 15:1 to 1:2, in particular 1:1 to 1:1.5, preferably 5:1 to 1:1 and preferentially 4:1 to 1:1. Likewise, according to this embodiment it is well shown that the inorganic binder is set, in particular before mixing with the organic binder, to a pH of less than 11, in particular less than 9, preferably less than 8.5. Preferably, the inorganic binder is set, in particular before mixing with the organic binder, to a pH value of less than 8, in particular in the range of pH 5 to pH 7.5.
[0036] In particular, in the mixtures of water glass and / or colloidal silicic acid with silane hydrolysates and / or silanes, a rather weak and low carbonation, i.e. the absorption of carbon dioxide from the air and the subsequent formation of carbonates, is observed, especially at pH values in the alkaline range. Carbonation, especially in the case of topcoats, leads to undesirable impairment of the surface properties, especially the appearance, by clouding the topcoat. The coating then often appears dusty, which is undesirable. Another advantage of the described mixtures is that the pH of the inorganic binder and / or coating composition can be set in the acidic range without precipitating silicates or silicic acid. Particularly good results are obtained in this respect when the inorganic binder is a silane-modified silicate compound or a silane-modified water glass, which is usually obtained by at least partially hydrolyzing and / or condensing at least one silane in the presence of at least one silicate at a pH of 8 or higher. Similarly, when silane-modified silicate compounds or silane-modified water glass are used, no carbonation is observed and the pH of the inorganic binder or coating composition can be set to a value of 7 or less without precipitating silicates. In this case, the pH can be adjusted by adding an acid. It is preferable to use silane-modified silicate compounds or silane-modified water glass in the neutral or acidic pH range, since the absorption of carbon dioxide, especially in the form of carbonate, is significantly reduced in the acidic range.
[0037] Preferably, the process for producing the silane-modified silicate or silane-modified water glass is carried out in such a way that the silane is at least partially hydrolyzed in the presence of a silicate compound or water glass at a pH of 8 or more, in particular above 11, to give the silane-modified silicate or water glass, and then the pH is set, in particular by adding an acid, to a value below 8.5, in particular below 8, preferably in the range from 4 to 7.
[0038] It is also possible to set a pH value between 2 and 4 during acidification, which can be achieved and maintained without causing precipitation or agglomeration of the silane-modified silicate compound or the silane-modified water glass. Only when the partial hydrolysis or condensation of silanes occurs in the presence of silicate in an alkaline aqueous solution, beneficial effects are already seen.However, often, the hydrolysis or condensation of silanes in the presence of silicate to form silane-modified silicate compounds or silane-modified water glass is completely carried out in alkaline.The partial hydrolysis of silanes and silicates in alkaline aqueous solution can be continued until hydrolysis is complete, if necessary, after acidification to pH 7 or less. Also according to this embodiment, in particular the above mentioned compounds lithium waterglass, sodium waterglass, potassium waterglass and mixtures thereof, preferably sodium waterglass, potassium waterglass and mixtures thereof, are used as waterglass or silicate.
[0039] For the preparation of silane-modified silicate compounds or water glass, epoxy-functional, phenoxy-functional, vinyl-functional or amino-functional silanes are advantageously used.More preferably, silanes having at least one Si-C bond, i.e., a bond between silicon and carbon atoms, are used.Different silanes can be used in mixtures with each other.Particularly suitable silanes are methacryloxymethyltrimethoxysilane, methacryloxymethyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and 3-mercaptopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-cyclohexyl ... Aminopropyltrimethoxysilane, N-cyclohexylamino-methyltriethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminomethylamino)propyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-ureidopropyltrimethoxysilane, vinyltrimethoxysilane, vinyldimethoxymethylsilane, vinyltriethoxysilane, vinyltriacetoxysilane, 3-methacryloyloxy Dipropyltrimethoxysilane, methacryloxymethyl)methyldimethoxysilane, methacryloxymethyltrimethoxysilane, 3-methacryloxypropyltriacetoxysilane, N-methyl[3-(trimethoxysilyl)propyl]carbamate, N-trimethoxysilylmethyl-O-methylcarbamate, N-dimethoxy(methyl)silylmethyl-O-methylcarbamate, tris-[3-(trimethoxysilyl)propyl]-isocyanurate, 3-glycidoxypropyltrimethoxysilane silane, 3-glycidoxypropyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane, isooctyltrimethoxysilane, isooctyltriethoxysilane, hexadecyltrimethoxysilane, (cyclohexyl)methyldimethoxysilane, dicyclopentyldimethoxysilane, phenyltriethoxysilane, triacetoxyethylsilane, and 1,2-bis(triethoxysilyl)ethane.
[0040] In the preparation of silane-modified silicate, silane and silicate are advantageously used in a mass ratio of 2:1 to 1:10, in particular 1:1 to 1:5, preferably 1:1 to 1:3, preferentially 1:1 to 1:2. Silane can be used as a single compound or as a mixture of silanes, the same applies to silicate. For further details of the preparation of silane-modified silicate or water glass, reference can be made to WO2016 / 107791, the disclosure of which is fully incorporated in the present invention.
[0041] If the coating composition comprises an inorganic binder, the coating composition typically comprises the inorganic binder in an amount of 1 to 30% by weight, in particular 2 to 25% by weight, preferably 3 to 20% by weight and preferentially 5 to 15% by weight, based on the coating composition. If the coating composition comprises an inorganic binder, it is often indicated that the coating composition comprises an organic binder in an amount of 1 to 40% by weight, in particular 2 to 30% by weight, preferably 3 to 25% by weight and preferentially 5 to 20% by weight, based on the coating composition. A combination of organic and inorganic binders provides the best results in accordance with the present invention. In the context of the present invention it is well indicated that the coating composition comprises a total binder content, i.e. the sum of organic binder and inorganic binder, in an amount of 2 to 70% by weight, in particular 5 to 60% by weight, preferably 10 to 50% by weight, preferably 15 to 40% by weight, based on the coating composition.
[0042] Thus, a preferred coating composition is (a1) an organic binder comprising a copolymer of at least one olefin and at least one unsaturated carboxylic acid; (a2) inorganic binders, and (b) Lubricant Includes. For this preferred embodiment of the invention, all particular characteristics, features and advantages discussed above in the context of further embodiments and properties apply as appropriate. According to a further preferred embodiment of the present invention, the coating composition comprises (a1) an organic binder comprising a copolymer of at least one olefin and at least one unsaturated carboxylic acid; (a2) an inorganic binder; (b) Lubricants, and (c) Thickeners and / or Rheological Additives Includes.
[0043] For this preferred embodiment of the invention, all particular characteristics, features and advantages discussed above in the context of further embodiments and properties apply as appropriate. According to a preferred embodiment of the present invention, therefore, (a1) an organic binder comprising a copolymer of at least one olefin and at least one unsaturated carboxylic acid; (a2) an inorganic binder; (b) a lubricant; (c) thickeners and / or rheological additives, and (d) Further Additives A coating composition is provided comprising: For this preferred embodiment of the invention, all advantages, properties and particular features mentioned above in the context of the further embodiments and properties of the coating composition of the invention apply as appropriate.
[0044] According to a preferred embodiment of the present invention, therefore, (a1) an organic binder comprising a copolymer of at least one olefin and at least one unsaturated carboxylic acid; (a2) an inorganic binder; (b) a lubricant; (c) thickeners and / or rheological additives; (d) further additives, and (e) Platelet-shaped particles A coating composition is provided comprising:
[0045] For this particular embodiment of the invention, all advantages, properties and particular features mentioned above in the context of further embodiments and properties of the invention apply as appropriate. It can further be provided that the coating composition comprises a filler. If the coating composition comprises a filler, the coating composition typically comprises the filler in an amount of 0.5 to 50% by weight, in particular 1 to 40% by weight, preferably 5 to 35% by weight and preferentially 10 to 30% by weight, based on the coating composition. Particularly good results are obtained when the filler is selected from calcium carbonate, barium sulfate, talc and mixtures thereof.
[0046] According to a preferred embodiment of the present invention, therefore, (a1) an organic binder comprising a copolymer of at least one olefin and at least one unsaturated carboxylic acid; (a2) an inorganic binder; (b) a lubricant; (c) thickeners and / or rheological additives; (d) further additives, and (e) Filler A coating composition is provided comprising: For this particular embodiment of the invention, all advantages, properties and particular features discussed above in the context of other embodiments and properties of the invention apply as appropriate.
[0047] According to a preferred embodiment of the present invention, therefore, (a1) an organic binder comprising a copolymer of at least one olefin and at least one unsaturated carboxylic acid; (a2) an inorganic binder; (b) a lubricant; (c) thickeners and / or rheological additives; (d) further additives; (e) platelet-shaped particles, and (f) Filler A coating composition is provided comprising:
[0048] For this particular embodiment of the invention, all advantages, properties and particular features mentioned above in the context of further embodiments and properties of the invention apply as appropriate. As already mentioned, the compositions of the invention are aqueous compositions, i.e. they contain water as a solvent or dispersant. Typically, the compositions of the invention contain water in an amount of 40 to 98% by weight, in particular 50 to 95% by weight, preferably 60 to 90% by weight and preferentially 60 to 85% by weight, based on the coating composition. Furthermore, the coating composition preferably contains only small amounts of organic solvents and volatile organic compounds (VOCs).Typically, the coating composition contains organic solvents and volatile organic compounds in an amount of less than 3% by weight, particularly less than 1% by weight, preferably less than 0.5% by weight, more preferably less than 0.3% by weight, particularly preferably less than 0.1% by weight, based on the coating composition.Preferably, the coating composition does not contain organic solvents and volatile organic compounds. As far as the viscosity of the coating composition of the invention is concerned, this can vary within a wide range. However, in the context of the invention, particularly good results are obtained if the coating composition has a Brookfield dynamic viscosity at 20° C. in the range of 2 to 5,000 mPas, in particular 5 to 1,000 mPas, preferably 5 to 500 mPas, preferentially 10 to 100 mPas and particularly preferably 30 to 50 mPas. With a viscosity in the abovementioned range, a particularly thin and uniform topcoat coating can be obtained.
[0049] The present invention Second A further subject of the present invention according to an embodiment is the use of the coating composition as described above as a topcoat for producing a coating having a selectively adjustable coefficient of friction on a metal substrate, in particular a metal substrate provided with a cathodic protection coating. For further details on this aspect of the invention, reference can be made to the descriptions of the other aspects of the invention, which are adapted according to the uses of the invention. Furthermore, the present invention Third Another subject matter of the invention according to an embodiment is a method for producing a coating having a tunable coefficient of friction, comprising the steps of: (a) in a first method step, a substrate having a cathodic protection coating applied to at least some areas is provided; (b) in a second method step after the first method step (a), a coating composition according to any one of claims 1 to 14 is applied to at least some areas of a substrate, and (c) in a third process step after the second process step (b), the coating composition applied in the second process step (b) is dried. In the context of the present invention it is particularly preferred that in a third method step (c) the coating composition applied to the substrate in the second method step (b) is cured and / or crosslinked.
[0050] Typically, the substrate comprises or consists of a metal. Preferably, the substrate consists of a metal. In this regard, particularly good results are obtained when the metal is selected from the group consisting of iron, aluminum, magnesium and mixtures and alloys thereof. In the context of the present invention it is particularly preferred that the metal is selected from iron and its alloys, in particular steel. In the context of the present invention, a substrate means an article that can be coated with a coating composition. Typically, in the context of the present invention, the substrate is selected from sheets, moldings, small parts and mixtures thereof. In light of this it is particularly preferred that the substrate is a small part, preferably a bulk material, in particular selected from screws, nuts, bolts, washers, rivets and mixtures thereof. In the context of the present invention it is particularly preferred that the substrate is a screw or a nut, in particular a bolt.
[0051] In particular with threads, a particular advantage of the coating composition and method of the invention, namely the particular setting of the coefficient of friction, is particularly effective. Insofar as the cathodic protection coating applied to the substrate over at least some area, and preferably the entire surface, is concerned, it typically comprises a metal selected from the group consisting of zinc, aluminum, magnesium, nickel, and mixtures and alloys thereof. Preferably, the cathodic protection coating comprises zinc and its alloys. In the context of the present invention, it is well indicated that the cathodic protection coating is selected from the group of zinc-containing coatings, in particular electroplated zinc coatings, in particular electroplated zinc-nickel coatings, hot-dip galvanized coatings, zinc powder coatings, in particular zinc paints, and zinc flake coatings. Preferably, the cathodic protection coating is selected from the group of electroplated zinc coatings, in particular electroplated zinc-nickel coatings, zinc powder coatings and zinc flake coatings. Zinc powder coatings and zinc flake coatings can in particular also comprise a zinc alloy. Preferably, the zinc alloy comprises, in addition to zinc, aluminum and / or magnesium, preferably aluminum and magnesium.
[0052] In the context of the present invention it is well indicated that in method step (b) the coating composition is applied to the substrate or to the cathodic protection coating in a layer thickness in the range from 1 to 12 μm, in particular from 1 to 10 μm, preferably from 1 to 8 μm, particularly preferably from 2 to 8 μm and very particularly preferably from 2 to 7 μm. The coating composition may be applied in process step (b) by any suitable method. However, in method step (b), the coating composition is usually applied to the substrate by spraying, brushing, rubbing, rolling, dipping or dipping-rolling. Particularly good results are obtained when the coating composition is applied to the substrate by dipping or dipping-rolling in method step (b). Dipping or dipping-rolling is particularly suitable for coating large amounts of material, such as small parts. In the context of the present invention, it is particularly preferred that the coating composition is applied over the entire surface of the substrate or cathodic protection coating.
[0053] The temperature at which the coating composition is dried in process step (c) can vary over a wide range depending on the substrate selected, the cathodic protection coating applied and the coating composition applied. However, it has been shown to be useful if in method step (c) the coating composition is dried at a temperature in the range of from 20 to 300°C, in particular from 30 to 250°C, preferably from 40 to 200°C, preferentially from 50 to 180°C, particularly preferably from 55 to 160°C and most preferably from 60 to 150°C. At such temperatures, rapid drying, or curing and / or crosslinking of the binder system usually occurs and decomposition of the organic binder is avoided. It has likewise been found to be advantageous if in process step (c) the coating composition is dried for a period of from 1 to 30 minutes, in particular from 2 to 25 minutes, preferably from 3 to 20 minutes and preferentially from 5 to 15 minutes.
[0054] As already mentioned, within the scope of the present invention, the coefficient of friction of the resulting coating, in particular the topcoat, can be set in a targeted manner. Thus, particularly good results are obtained when the coefficient of friction of the coated substrate, measured according to DIN EN ISO 16047:2013-01, is set in the range of 0.09 to 0.16 by applying the coating composition. The coefficient of friction is set in particular by the amount of organic binder and the type and amount of lubricant. For further details regarding this aspect of the invention, reference may be made to the above descriptions of the other aspects of the invention, which are appropriately adapted according to the methods of the invention. Finally, the present invention Fourth A further subject of the present invention according to an embodiment is a metal substrate, in particular obtainable by a coating composition as described above or a method as described above.
[0055] Typically, the substrate still has a coating, i.e., a cured coating composition, particularly a topcoat, and especially a cathodic protection coating, between the basecoat forms. In the context of the invention, it is preferred that the coating comprises a lubricant in an amount of 1 to 25% by weight, in particular 1 to 20% by weight, preferably 1.5 to 17% by weight, preferentially 2 to 15% by weight and particularly preferably 2.5 to 12% by weight, based on the coating. Typically, the coating, in particular the topcoat, comprises an organic binder in an amount of 60 to 99% by weight, in particular 65 to 99% by weight, preferably 70 to 98% by weight, preferentially 75 to 97% by weight and particularly preferably 80 to 96% by weight, based on the coating, in particular the topcoat. In the context of the present invention, when a mixture of organic and inorganic binders is used, it is well indicated that the coating, in particular the topcoat, comprises the organic binder in an amount of 25 to 70% by weight, in particular 30 to 65% by weight, preferably 35 to 60% by weight, preferentially 40 to 55% by weight and particularly preferably 43 to 53% by weight, based on the coating, in particular the topcoat. Likewise, in the context of the invention according to this embodiment, it is preferred that the coating, in particular the topcoat, comprises an inorganic binder in an amount of 25 to 70% by weight, in particular 30 to 65% by weight, preferably 35 to 65% by weight, preferentially 40 to 55% by weight and particularly preferably 43 to 53% by weight, based on the coating, in particular the topcoat.
[0056] It is furthermore well indicated that the weight ratio of organic binder to inorganic binder is in the range of 1.5:1 to 1:2, in particular 1.5:1 to 1:1.5, preferably 1.1:1 to 1:1.1, based on the weight of organic binder and the weight of inorganic binder in the coating, in particular the topcoat. It is also preferred that the coating, in particular the topcoat, comprises platelet-shaped particles in an amount of 0.5 to 20, in particular 1 to 15% by weight, preferably 1.5 to 12% by weight, preferentially 1.5 to 10% by weight, based on the coating, in particular the topcoat. In light of this, particularly good results are obtained if the coating comprises a total amount of lubricant and platelet-shaped particles in the range of 1.5 to 45% by weight, in particular 2 to 35% by weight, preferably 3.5 to 25% by weight and preferentially 4 to 20% by weight, based on the coating composition. The coating, in particular the topcoat, therefore preferably has a layer thickness in the range from 1 to 10 μm, in particular from 1 to 8 μm, preferably from 1 to 7 μm, preferentially from 2 to 7 μm and particularly preferably from 2 to 6 μm.
[0057] Furthermore, it is preferred that the coefficient of friction, measured according to DIN EN ISO 16047:2013-01, of the coated substrate varies in the range from 0.09 to 0.16. For further details regarding the substrate of the present invention, reference can be made to the above descriptions of other aspects of the present invention, which apply appropriately with respect to the substrate of the present invention. The subject matter of the present invention is explained below with reference to embodiments in an illustrative, non-limiting manner. EXAMPLES
[0058] To further illustrate the invention and its advantages, several series of tests were carried out with the topcoat composition of the invention applied to threads, the sliding and frictional properties of which were then measured. 1. Examples 1 to 3 First, the properties of a topcoat composition containing only an organic binder based on an acrylate / methacrylate / styrene copolymer are investigated. Micronized polyethylene wax and thickeners (RheoByk 7420 ES and Optigel) are added to the composition. The coating composition is shown in Table 1 below.
[0059] [Table 1]
[0060] The coating composition is applied to the entire surface of the thread with a layer thickness of 7 μm using a dip roller and then dried at 120° C. for 20 minutes. The screw is then subjected to a friction coefficient measurement in accordance with DIN EN ISO 16047:2013-01. Both the total friction coefficient and the friction coefficient of the head and thread separately are found to lie within the specified VDA window of 0.09 to 0.16. For further investigation, multiple clamping (5 clamps) was carried out on steel surfaces, on surfaces with organic cathodic dip coating (KTL) and on aluminum surfaces. It is shown that a multiple fitting friction coefficient window is only observed on steel. All three coating compositions show excellent heat dissipation behavior. The values are shown in Table 2 below.
[0061] [Table 2]
[0062] 2. Examples 4 and 5 In addition to tests 1-3 above, tests were carried out using acrylic copolymers as binders. The compositions are shown in Table 3 below, and the tests of friction and slip properties in Table 4 below. From Table 4 it can also be seen that the hot soldering properties of compositions 4 and 5 are excellent. The coefficients of friction are also always within the VDA window. This is also the case for multiple fastenings both in steel, KTL and aluminum.
[0063] [Table 3]
[0064] [Table 4]
[0065] 3. Examples 6 to 9 In Examples 6 to 9, a mixture of an organic ethylene-acrylic acid copolymer and an inorganic binder in the form of a colloidal silica sol is used. A thickener and a micronized polyethylene wax are added to each of Compositions 6 to 9 in an amount of 1% by weight. The compositions are shown in Table 5 below. The compositions are reapplied to the threads and their friction properties are tested. The test results are shown in Table 6 below. It can be seen that the coefficient of friction is always within the desired VDA window.
[0066] [Table 5]
[0067] [Table 6]
[0068] 4. Examples 10 to 17 Furthermore, two series of tests were carried out, one using an organic binder based on an acrylic acid copolymer (Examples 10-13) and a second series of tests using an inorganic binder in the form of a colloidal silica sol (Examples 14-17). Compositions of test system 1 (Examples 10 to 13) are shown in Table 7, and examples of test system 2 (Examples 14 to 17) are shown in Table 9. The compositions are each applied to a bolt and tested for their sliding and frictional properties. The results of these tests are shown in Tables 8 and 10. Both topcoats 10-13, which contain purely organic binders, and topcoats 14-17, which contain a mixture of organic and inorganic binders, are shown to have excellent properties. All topcoats meet the VDA specifications in terms of coefficient of friction, total coefficient of friction, head coefficient of friction and thread coefficient of friction. The heat release behavior is also always acceptable.
[0069] [Table 7]
[0070] [Table 8]
[0071] [Table 9]
[0072] [Table 10]
[0073] 5. Examples 18 to 28 Additionally, tests are conducted with binder systems including an organic binder in the form of an acrylic copolymer and an inorganic binder in the form of a colloidal silica sol, with various lubricants added. Using a dip roller, the coating composition is applied to the entire surface of the thread in a layer thickness of 7 μm and then dried at 150° C. for 30 minutes. The screws are then subjected to a coefficient of friction measurement in accordance with DIN EN ISO 16047:2013-01.
[0074] [Table 11]
[0075] [Table 12]
[0076] [Table 13]
[0077] [Table 14]
Claims
1. 1. An aqueous coating composition for producing a coating, particularly a top coat, having a tunable coefficient of friction, comprising: (a) an organic binder comprising a copolymer of at least one unsaturated hydrocarbon and at least one unsaturated carboxylic acid; and (b) Lubricant A coating composition comprising:
2. 2. Coating composition according to claim 1, characterized in that the unsaturated hydrocarbon is selected from the group consisting of aliphatic hydrocarbons having a vinyl group, aromatic hydrocarbons having a vinyl group, aliphatic hydrocarbons having an alkynyl group, aromatic hydrocarbons having an alkynyl group and mixtures thereof, in particular aliphatic hydrocarbons having a vinyl group, aromatic hydrocarbons having a vinyl group and mixtures thereof, preferably aliphatic hydrocarbons having a vinyl group.
3. The unsaturated hydrocarbon is an aliphatic and / or aromatic C 2 -C 20 Compounds, aliphatic and / or aromatic C having vinyl groups 2 -C 20 Compounds and mixtures thereof, in particular aliphatic and / or aromatic C 2 -C 12 Compounds, aliphatic and / or aromatic C having vinyl groups 2 -C 12 Compounds and mixtures thereof, preferably aliphatic and / or aromatic C 2 -C 10 Compounds, aliphatic and / or aromatic C having vinyl groups 2 -C 10 Compounds and mixtures thereof, preferentially aliphatic and / or aromatic C 14 containing alkynyl groups 2 -C 8 Compounds, aliphatic and / or aromatic C having vinyl groups 2 -C 8 Compounds and mixtures thereof, particularly aliphatic C 1 compounds with vinyl groups 2 -C 6 compounds, more preferentially aliphatic C 2 -C 4 Alkenes, particularly preferably C 2 and C 3 2. The coating composition of claim 1, wherein the at least one alkenes are selected from the group consisting of alkenes.
4. The unsaturated carboxylic acid is 2 -C 20 Alkenic acids, especially C 2 -C 12 Alkenic acid, preferably C 2 -C 10 Alkenic acids, preferentially C 2 -C 4 Alkenic acids, more preferentially C 2 and C 3 2. The coating composition of claim 1, wherein the base is selected from alkenoic acids and their esters and amides.
5. The unsaturated carboxylic acid is acrylic acid, acrylic acid and C 1 -C 10 Esters with alcohol, methacrylic acid, methacrylic acid and C 1 -C 10 Esters with alcohols, fumaric acid, maleic acid, especially acrylic acid, acrylic acid and C 1 -C 10 Esters of alcohols, methacrylic acid and methacrylic acid with C 1 -C 10 2. The coating composition according to claim 1, characterized in that it is selected from the group of esters with alcohols.
6. 2. Coating composition according to claim 1, characterized in that it comprises the organic binder in an amount of 2 to 70% by weight, in particular 5 to 60% by weight, preferably 10 to 50% by weight and preferentially 10 to 40% by weight, based on the coating composition.
7. 2. Coating composition according to claim 1, characterized in that the lubricant is selected from the group of organic lubricants, inorganic lubricants and mixtures thereof, preferably organic lubricants.
8. 2. Coating composition according to claim 1, characterized in that the lubricant is selected from the group of waxes, graphene, graphite, boron nitride, molybdenum disulfide, plastic particles, in particular polyetherketone (PEK), polyetheretherketone (PEEK), polyphenylene sulfide (PPS), polyethersulfone (PES), polyetherimide (PEI), polyamideimide (PAI) and mixtures thereof, micronized sulfur and mixtures thereof, preferably waxes.
9. 2. Coating composition according to claim 1, characterized in that it comprises the lubricant in an amount of 0.1 to 10% by weight, in particular 0.3 to 8% by weight, preferably 0.5 to 5% by weight and preferentially 0.8 to 4% by weight, based on the coating composition.
10. 2. The coating composition according to claim 1, characterized in that it is free of fluorine-containing compounds, in particular free of organic fluorine-containing compounds.
11. 10. The coating composition of claim 1, comprising platelet-shaped particles.
12. The coating composition of claim 1 , further comprising an inorganic binder.
13. 13. The coating composition of claim 12, wherein the inorganic binder is selected from silanes, silane hydrolysates, silicates, polysiliconates, and mixtures thereof.
14. (a1) an organic binder comprising a copolymer of at least one olefin and at least one unsaturated carboxylic acid; (a2) an inorganic binder, and (b) Lubricant 13. The coating composition of claim 12, comprising:
15. 15. Use of a coating composition according to any one of claims 1 to 14 as a topcoat for producing a coating with an adjustable coefficient of friction on a metal substrate, in particular a metal substrate provided with a cathodic protection coating.
16. 1. A method for producing a coating having a selectively tunable coefficient of friction, comprising: (d) in a first method step, a substrate is provided having a cathodic protection coating applied to at least some areas; (e) in a second method step after the first method step (a), a coating composition according to any one of claims 1 to 14 is applied to at least some areas of the substrate; and (f) in a third method step after the second method step (b), the coating composition applied in the second method step (b) is dried; A method characterized by:
17. 17. The method according to claim 16, characterized in that the coefficient of friction of the coated substrate, measured according to DIN EN ISO 16047:2013-01, is set in the range of 0.09 to 0.
16.
18. Metal substrate comprising a coating, in particular obtainable with a coating composition according to any one of claims 1 to 14.
19. 19. The metal substrate according to claim 18, characterized in that the coating comprises the lubricant in an amount of 1 to 25% by weight, in particular 1 to 20% by weight, preferably 1.5 to 17% by weight, preferentially 2 to 15% by weight, particularly preferably 2.5 to 12% by weight, based on the coating.
20. 19. The metal substrate according to claim 18, characterized in that the coating comprises the organic binder in an amount of 60 to 99% by weight, in particular 65 to 99% by weight, preferably 70 to 98% by weight, preferentially 75 to 97% by weight, particularly preferably 80 to 96% by weight, based on the coating.
